BIOMARKER PADA LUPUS NEFRITIS - Gisela Tania Irwanto; Yuswanto Setyawan (Bahasa Indonesia, 2023)
Lupus nephritis (LN) continues to be a leading cause of high morbidity and mortality rates in systemic lupus erythematosus (SLE) patients. Kidney biopsy remains the gold standard for diagnosing LN. Several biomarkers have been identified and evaluated, contributing to improvements in the management of LN patients. This literature review summarizes recent relevant literature on biomarkers for the diagnosis, monitoring, and prognosis of LN. These biomarkers are categorized based on their sample sources, namely serum and urine. Both sample sources show significant variations in biomarker data associated with disease activity and histological parameters of LN. Potential biomarker molecules include antibodies, cytokines, chemokines, and adhesion molecules. This literature review provides a general overview and serves as a reference for further research, particularly in advancing the understanding of LN biomarkers in Indonesia. Keywords: systemic lupus erythematosus (SLE), lupus nephritis (LN), biomarkers, serum, urin